2013
DOI: 10.1042/cs20120663
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I (IGF-I) and clinical nutrition

Abstract: IGF-I (insulin-like growth factor-I) is a peptide hormone, produced predominantly by the liver in response to pituitary GH (growth hormone), which is involved in a wide variety of physiological processes. It acts in an endocrine, paracrine and autocrine manner to promote growth. The production of IGF-I signals the availability of nutrients needed for its anabolic actions. Recently, there has been growing interest in its role in health and disease. IGF-I has long been known to be regulated by nutrition and dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 171 publications
1
56
0
Order By: Relevance
“…Insulin-like growth factor-1 (IGF-1), which is mainly produced by the liver, participates in diverse physiological processes [93]. The in vitro and in vivo studies showed that the interaction of IGF-1 and IGF-1R is essential for cell growth and survival of various transformed cells [94].…”
Section: Furin Promotes Cell Proliferation and Ecm Synthesis By Activmentioning
confidence: 99%
“…Insulin-like growth factor-1 (IGF-1), which is mainly produced by the liver, participates in diverse physiological processes [93]. The in vitro and in vivo studies showed that the interaction of IGF-1 and IGF-1R is essential for cell growth and survival of various transformed cells [94].…”
Section: Furin Promotes Cell Proliferation and Ecm Synthesis By Activmentioning
confidence: 99%
“…Previous observations also found that addition of KDF to the diet improved growth performance in post-weaning piglets (Paulicks et al, 2000;Htoo and Molares, 2012), and increased ADG and ADFI in growing-finishing pigs (Overland et al, 2000;Mroz et al, 2002). Furthermore, the expression of IGF-I from peripheral tissue is also GH dependent, it plays an important role in body growth via autocrine/paracrine manner (Livingstone, 2013). Iresjö et al (2013) observed that re-synthesis of muscle proteins following starvation is not critically dependent on endocrine liver-derived IGF-I.…”
Section: Discussionmentioning
confidence: 88%
“…Dysfunction in the GH axis is difficult to estimate in basal blood samples since IGF-1 level is not regulated by GH alone, but also by other factors such as insulin level and nutritional status [25]. Provocative testing of the GH axis, such as testing of GH response to insulin-induced hypoglycemia or arginine and GH releasing hormone in combination, is critical to diagnosing GH deficiency.…”
Section: Discussionmentioning
confidence: 99%